Efficient composite fresh-keeping material and application thereof in fresh keeping of peach fruits
The preparation of efficient composite fresh-preserving materials through multi-fluid coaxial electrospinning technology has solved the problems of high cost, high technical requirements and limited fresh-preservation effects in existing peach fruit fresh-preservation technology, and achieved the effect of significantly extending the storage time of peach fruit and ensuring quality.
Patent Information
- Application Number
- CN202510253761.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-25
AI Technical Summary
The existing peach fruit preservation technology has the problems of high equipment costs, high technical requirements and limited preservation effects, and the commonly used preservation agents have problems with safety and low consumer acceptance.
Multi-fluid coaxial electrospinning technology is used to prepare efficient composite fresh-preserving materials. The material consists of chitin nanocrystals, hydrogels and bacterial cellulose-chitosan to form a sandwich structure to enhance the fresh-preserving effect, and tea polyphenols, thyme and licorice extracts are added to inhibit the growth of harmful microorganisms.
Significantly extend the storage time of peach fruits, ensure good quality during storage, reduce nutrient loss and rot risks, and improve the stability and antibacterial properties of fresh-preserving materials.
Smart Images

Figure CN119877197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food preservation, and in particular relates to a high-efficiency composite fresh-keeping material and application thereof in peach fruit preservation. Background Art
[0002] Peach is a drupe of the genus Prunus in the Rosaceae family. It is popular for its delicious taste, rich nutritional value and variety of varieties. Peach fruits are usually round or nearly spherical, of different sizes, with a variety of peel colors, fine flesh, rich juice, sweet taste and aroma. Peach contains a variety of nutrients that are beneficial to the human body, such as protein, fat, dietary fiber, pectin, organic acid, carotene, niacin and other bioactive substances, which have antioxidant, anti-aging and immune-enhancing effects. Peach fruit is a drupe fruit with a respiratory climacteric rate. It is very easy for microorganisms to breed after harvest, causing softening, rot and quality deterioration. Due to its high water content and soft and juicy flesh, the respiration intensity increases rapidly after harvest, causing the fruit to lose its edible value in a short period of time, increasing the risk of foodborne diseases. In addition, peach fruit is sensitive to low temperatures and is prone to chilling damage during low-temperature storage, which manifests as browning of the flesh, hardening of the texture, loss of flavor, etc., which aggravates the decay and quality decline of the fruit. Therefore, ensuring the freshness of peach fruits after harvest can reduce the post-harvest storage logistics losses and fresh consumption risks of fruits and vegetables caused by pathogenic microorganisms. The application of existing peach fruit preservation technologies has certain limitations. For example, low-temperature refrigeration, controlled atmosphere storage, and pre-cooling treatment can delay the aging of peach fruits, but these methods often require high equipment costs and technical requirements, and the preservation effect is limited. In addition, the application of preservatives in peach fruit preservation also faces many challenges. Currently, commonly used preservatives such as exogenous hormones and phenolic acid compounds can delay softening and water loss, but their effects weaken with the extension of storage time, and there are safety issues. In addition, some preservatives are difficult to promote in actual applications due to high costs, complex operations, or low consumer acceptance. Therefore, it is urgent to study new peach fruit preservation methods to ensure the good quality of peach fruits during storage and transportation after harvest. Summary of the invention
[0003] Technical problems to be solved: In view of the above technical problems, the purpose of the present invention is to provide a high-efficiency composite fresh-keeping material and its application in peach fruit preservation, which is made of chitin nanocrystal solution, hydrogel solution, bacterial cellulose-chitosan solution using multi-fluid coaxial electrospinning technology to prepare the composite fresh-keeping material, and applied to peach fruit preservation. The chitin nanocrystals in the inner layer of the composite fresh-keeping material prepared by the present invention and the outer layer chitosan with positive charge and the negative charge of the middle layer xanthan gum interact electrostatically, strengthening the close connection between the composite fresh-keeping materials; in addition, the chitin nanocrystals form a semipermeable membrane, the dialdehyde xylose cross-links the xanthan gum to form a gel network and a cross-linked network of bacterial cellulose-chitosan, which can form a barrier to the respiration of peach fruits, allow oxygen to seep out to ensure that water is not lost, inhibit the respiration of peach fruits after harvesting and storage, reduce the loss of nutrients in peach fruits, and tea polyphenols + thymol + licorice extract can inhibit the growth and reproduction of harmful microorganisms, ensuring the freshness and good quality of peach fruits.
[0004] Technical solution: A method for preparing a high-efficiency composite fresh-keeping material, comprising the following steps: S1. The bacterial cellulose solution and the chitosan solution were stirred and mixed uniformly, and then borate was added for cross-linking to prepare a bacterial cellulose-chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution having a mass fraction of 0.5-2.5%; S3. dissolving xanthan gum, dialdehyde xylose, acrylate and preservative complex uniformly, treating at 50-60° C. for 30-75 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, a high-efficiency composite fresh-keeping material was prepared by multi-fluid coaxial electrospinning technology. Furthermore, in step S1, the concentration of the chitosan solution is 1.5-4.0 wt%, and the concentration of the bacterial cellulose solution is 0.5-3 wt%. Furthermore, in step S1, the ratio of the bacterial cellulose solution to the chitosan solution is 1:(4-8). Furthermore, the amount of borate added in step S1 is 2-4 wt%. Furthermore, in step S3, the amount of xanthan gum added is 1-3wt%, the amount of dialdehyde xylose added is 1.5-2.5wt%, and the amount of acrylate added is 1-4wt%. Furthermore, the amount of the preservative compound added in step S3 is 5-10%, and the composition of the preservative compound is tea polyphenols + thymol + licorice extract, wherein the ratio of tea polyphenols: thymol: licorice extract is (1-3): (0.5-2.5): (1-4). Furthermore, the specific conditions of the multi-fluid coaxial electrospinning technology in step S4 are: the outer layer spinning solution flow rate is 1.0-5.0 mL / h, the middle layer spinning solution flow rate is 1.0-2.0 mL / h, and the inner layer spinning solution flow rate is 0.1-1.0 mL / h. The high-efficiency composite fresh-keeping material obtained by any of the preparation methods described above. Furthermore, the high-efficiency composite fresh-keeping material is used in food preservation. Furthermore, the high-efficiency composite fresh-keeping material is used in the preservation of peach fruits. Beneficial effects: 1. The high-efficiency composite fresh-keeping material prepared by the multi-fluid coaxial electrospinning technology of the present invention contains a "sandwich structure", wherein the outer layer is composed of bacterial cellulose and chitosan, the middle layer is a xanthan gum hydrogel containing tea polyphenols + thymol + licorice extract, and the inner layer is chitin nanocrystals; chitosan and chitin nanocrystals themselves are positively charged, and there is electrostatic interaction with the negative charge of xanthan gum, thereby strengthening the close combination between the high-efficiency composite fresh-keeping materials; on the one hand, the amino groups contained in chitosan and chitin can interact with the carboxyl and hydroxyl groups in xanthan gum to form electrostatic complexes and hydrogen bonds, respectively; on the other hand, the hydroxyl groups of xanthan gum in the xanthan gum hydrogel and the aldehyde groups of dialdehyde xylose undergo condensation reactions to form stable covalent bonds for cross-linking, thereby enhancing the stability and mechanical strength of the hydrogel, thereby improving the stability and mechanical properties of the structure of the high-efficiency composite fresh-keeping material. 2. The chitin nanocrystals in the inner layer structure of the high-efficiency composite fresh-keeping material prepared in the present invention form a semipermeable membrane on the surface of the peach fruit, which allows oxygen to pass through and prevents carbon dioxide from passing through and water loss. The inner layer structure forms a high-concentration carbon dioxide environment, which prevents the respiration of the peach fruit and reduces the degradation of sugar substances in the peach fruit; the xanthan gum hydrogel in the high-efficiency composite fresh-keeping material can be tightly adsorbed on the semipermeable membrane formed by the chitin nanocrystals, and the tea polyphenols, thymol and licorice extract can synergistically inhibit the cell membrane integrity of harmful microorganisms, interfere with their normal energy metabolism and inhibit the synthesis of key substances. The licorice extract induces harmful microorganisms to produce active oxygen free radicals, which can trigger the chain polymerization of acrylates to form a long-chain polymer structure, which is interspersed in the xanthan gum hydrogel network structure to form a cross-linked network, and solidifies the hydrogel structure of the high-efficiency composite fresh-keeping material, so that it can stably play a fresh-keeping and antibacterial role; the cross-linked network formed by bacterial cellulose and chitosan can effectively prevent water loss and oxygen infiltration, slow down the oxidation of peach fruits and the invasion of harmful microorganisms, and at the same time inhibit the growth and reproduction of harmful microorganisms, thereby ensuring the freshness and storage time of the peach fruits. 3. The high-efficiency composite fresh-keeping material prepared by the present invention can significantly prolong the storage time of peach fruit and ensure the good quality of peach fruit during storage. It not only provides a new theoretical reference for the fresh-keeping method of peach fruit, but can also be extended to the fresh-keeping application of other types of food. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The antibacterial activity of Example 1 and Comparative Examples 1-4; Figure 2 The changes in the decay rate of peaches during storage in Example 1 and Comparative Examples 1-4 are shown; Figure 3 The changes in weight loss rate of peaches during storage in Example 1 and Comparative Examples 1-4 are shown; Figure 4 The changes in the hardness of the peaches during storage in Example 1 and Comparative Examples 1-4; Figure 5 The changes in soluble solid content of Example 1 and Comparative Examples 1-4 during the storage of peaches; Figure 6 The changes in appearance evaluation of the peaches during storage of Example 1 and Comparative Examples 1-4 are shown; Figure 7 The changes in the malondialdehyde content of Example 1 and Comparative Examples 1-4 during the storage of peaches. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 2 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 4 wt % bacterial cellulose solution and 300 g of a 2 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 3 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 250 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 6 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 50 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 4 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 400 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 9 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 50 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 5 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 40 g of a 2 wt % bacterial cellulose solution and 240 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 11.2 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 6 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution having a mass fraction of 1%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 50 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 7 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 20 g of xanthan gum, 20 g of dialdehyde xylose, 20 g of acrylate and 55 g of preservative complex (11 g of tea polyphenols + 22 g of thymol + 22 g of licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 8 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 9 g xanthan gum, 12 g dialdehyde xylose, 20 g acrylate and 42 g preservative complex (14 g tea polyphenols + 10.5 g thymol + 17.5 g licorice extract) were uniformly dissolved in 600 mL of water and treated at 60 ° C for 50 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 9 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 60 g of a 2 wt % bacterial cellulose solution and 360 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 8.4 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 14 g thymol + 42 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Example 10 A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.5mL / h, and the inner layer spinning solution flow rate is 1.0mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Comparative Example 1 The difference between this comparative example and Example 1 is that xanthan gum hydrogel is not used. A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed uniformly, and then 7 g of borate was added for cross-linking, and then 70 g of a preservative complex (14 g of tea polyphenols + 28 g of thymol + 28 g of licorice extract) was dissolved uniformly to prepare a bacterial cellulose-chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. Using bacterial cellulose-chitosan solution as the outer spinning solution and chitin nanocrystal solution as the inner spinning solution, the outer spinning solution flow rate is 5.0 mL / h and the inner spinning solution flow rate is 1.0 mL / h, and multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite fresh-keeping materials. Comparative Example 2 The difference between this comparative example and Example 1 is that chitin nanocrystals are not used. A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S3. Using bacterial cellulose-chitosan solution as the outer spinning solution and hydrogel solution as the inner spinning solution, the outer spinning solution flow rate is 5.0 mL / h and the inner spinning solution flow rate is 1.0 mL / h, and multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Comparative Example 3 The difference between this comparative example and Example 1 is that bacterial cellulose and chitosan are not used. A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S2. 15 g xanthan gum, 20 g dialdehyde xylose, 20 g acrylate and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S3. Using hydrogel solution as the outer spinning solution and chitin nanocrystal solution as the inner spinning solution, the outer spinning solution flow rate is 5.0 mL / h and the inner spinning solution flow rate is 1.0 mL / h, and multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Comparative Example 4 The difference between this comparative example and Example 1 is that no acrylate is added. A method for preparing a high-efficiency composite fresh-keeping material comprises the following steps: S1. 50 g of a 2 wt % bacterial cellulose solution and 300 g of a 1.5 wt % chitosan solution were stirred and mixed, and then 7 g of borate was added for cross-linking to prepare a bacterial cellulose - chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution with a mass fraction of 2%; S3. 15 g xanthan gum, 20 g dialdehyde xylose and 70 g preservative complex (14 g tea polyphenols + 28 g thymol + 28 g licorice extract) were uniformly dissolved in 1 L of water and treated at 60 ° C for 60 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, the outer layer spinning solution flow rate is 5.0mL / h, the middle layer spinning solution flow rate is 1.0mL / h, and the inner layer spinning solution flow rate is 0.5mL / h. Multi-fluid coaxial electrospinning technology is used to prepare high-efficiency composite preservative materials. Performance Testing (1) Mechanical properties The mechanical properties of Examples 1-10 and Comparative Examples 1-4 were tested at room temperature using a tensile testing machine. First, the high-efficiency composite fresh-keeping material was precisely cut into strips of 50 mm in length and 4 mm in width. The tensile rate was 5 mm / min, and the tensile strength and elongation at break were calculated. Table 1 Tensile strength and elongation at break of Examples 1-10 and Comparative Examples 1-4 As can be seen from Table 1, the tensile strength and elongation at break of Examples 1-10 are higher than those of Comparative Examples 1-4, among which the tensile strength and elongation at break of Example 1 are the largest, indicating that the high-efficiency composite fresh-keeping material prepared in Example 1 has the best mechanical properties. (2) Antibacterial properties Take a loopful of Staphylococcus aureus and Escherichia coli and inoculate it into the liquid culture medium, place it in a shaker and shake for 12 hours at 37°C and 120 r / min. The obtained microbial culture medium is diluted to 10% with 0.9% sterile saline. 5 -10 6 CFU / mL; the composite membrane was punched into a disc with a diameter of 6 mm, sterilized under ultraviolet light for 30 minutes, 50ul of the diluted bacterial solution was evenly applied to the solid culture medium, the sample membrane was placed on the solid culture medium and marked; after sealing, it was placed in a biochemical incubator for breeding for 24 hours. Depend on Figure 1 It can be seen that the antibacterial rate of the high-efficiency composite fresh-keeping material prepared in Example 1 against Staphylococcus aureus and Escherichia coli is higher than that in Comparative Examples 1-4, wherein Comparative Example 1 does not use xanthan gum hydrogel, and the positive charge of the chitin nanocrystals in the inner layer structure of the material and the positive charge of the chitosan in the outer layer structure produce electrostatic repulsion, which affects the stability of the high-efficiency composite fresh-keeping material and thus affects its antibacterial performance; Comparative Examples 2 and 3 do not use chitin nanocrystals or bacterial cellulose-chitosan respectively, although the high-efficiency composite fresh-keeping material will not be affected by electrostatic repulsion on the structural stability, the fresh-keeping material is easily polluted by the external environment, thereby affecting its antibacterial performance; Comparative Example 4 does not add acrylate, and the xanthan gum hydrogel in the middle layer structure of the licorice extract high-efficiency composite fresh-keeping material has a certain fluidity, and tea polyphenols, thymol and licorice extract are in a flowing state in the hydrogel, rather than being firmly fixed in the high-efficiency composite fresh-keeping material to play a stable and efficient role, so compared with Example 1, its antibacterial performance is affected. (3) Experiment on the preservation of peaches using high-efficiency composite fresh-keeping materials Peach fruits of similar size and color, without mechanical damage and disease infection were selected, cleaned, air-dried, and randomly divided into 6 groups, with 20 fruits in each group. Each group was treated as follows: A: No treatment is used, blank control; B: The composite cling film prepared in Example 1 was used for packaging, which was recorded as Example 1 group; C: The composite cling film prepared in Comparative Example 1 was used for packaging, recorded as Comparative Example 1; D: The composite cling film prepared in Comparative Example 2 was used for packaging, recorded as Comparative Example 2; E: The composite cling film prepared in Comparative Example 3 was used for packaging, recorded as Comparative Example 3; F: The composite cling film package prepared in Comparative Example 4 is used, recorded as Comparative Example 4 group; All treatment groups were stored at high temperature (35±1℃) for 7 days, and the peach indicators were measured every other day. The indicators included rot rate, weight loss rate, hardness, soluble solids, and appearance evaluation. The measurement methods were as follows: ①Rot rate: rot rate (%) = number of rotten fruits / total number of samples × 100%; ② Weight loss rate: The weight loss rate of peaches was measured by weighing method, weight loss rate (%) = (W1-W2) / W1×100%, where W1 is the weight of peaches before treatment, and W2 is the weight of peaches at each measurement; ③Hardness: Use a hardness tester to measure the hardness of peaches; ④Soluble solids: When measuring, squeeze out the peach juice with gauze and use a handheld refractometer to measure the soluble solids; ⑤ Appearance evaluation: 10 professionals were selected as judges to conduct a comprehensive evaluation of the appearance, color, mildew rate, and smell of the peaches. The appearance evaluation of the peaches is shown in Table 2; ⑥ Malondialdehyde content: Determined by thiobarbituric acid (TBA) method, extracted with trichloroethanol, then boiled with thiobarbituric acid and determined. Table 2 Peach appearance evaluation table score Appearance Color Mildew rate (%) odor 5 The fruit is full and hard Bright colors 0-20 Rich fruity aroma 4 The fruit is full and hard on the outside Slightly lighter color 20-40 Slightly fruity 3 The skin shrinks and becomes soft Darkening 40-60 No fragrance 2 Partially rotten Partial browning 60-80 sour smell 1 All rotten All black 80-100 Moldy smell Depend on Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7It can be seen that the peaches packaged with the high-efficiency composite fresh-keeping material prepared in Example 1 were stored at 35°C for 7 days, and the decay rate, weight loss rate, hardness, soluble solid content, appearance evaluation and malondialdehyde content as the storage time changed were better than those of Comparative Examples 1-4, and maintained a high edible quality and freshness, indicating that on the one hand, the semipermeable membrane formed by the chitin nanocrystals in the inner layer structure of the high-efficiency composite fresh-keeping material is attached to the surface of the peaches, allowing oxygen to seep out and preventing water loss, and the bacterial cellulose-chitosan cross-linked network in the outer layer hinders oxygen penetration, inhibits the respiration of the peaches after harvesting, and avoids increasing the loss of nutrients, so the soluble solid loss and weight loss rate during storage are relatively small; on the other hand, the fresh-keeping compound (tea polyphenols + thymol + licorice extract) in the high-efficiency composite fresh-keeping material can destroy the integrity of the cell membrane of harmful bacteria and It can hinder the synthesis of key substances for the growth of harmful bacteria, thereby inhibiting the growth and reproduction of harmful bacteria in the external environment on the surface of peaches. In addition, licorice extract can induce a large number of active oxygen free radicals in the cells of harmful bacteria, triggering the free radical chain polymerization reaction of acrylate to form long polymer chains, which are interspersed in the xanthan gum hydrogel network structure, solidifying the hydrogel network structure, and further strengthening the close connection between the layers of the high-efficiency composite fresh-keeping material. It can also fix the harmful bacteria on the high-efficiency composite fresh-keeping material for targeted killing and inhibition of bacteria. At the same time, bacterial cellulose can work synergistically with the fresh-keeping composite, and its functional groups such as hydroxyl and carboxyl interact with the phospholipid components of the cell membrane of harmful bacteria, destroying the integrity of the cell membrane and inhibiting the reproduction of harmful bacteria, thereby reducing the rot rate and malondialdehyde production of peaches, and ensuring the appearance quality of peaches for storage and consumption. The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a high-efficiency composite fresh-keeping material, characterized in that: The following steps are involved: S1. The bacterial cellulose solution and the chitosan solution were stirred and mixed uniformly, and then borate was added for cross-linking to prepare a bacterial cellulose-chitosan solution; S2. dissolving chitin nanocrystals to prepare a chitin nanocrystal solution having a mass fraction of 0.5-2.5%; S3. dissolving xanthan gum, dialdehyde xylose, acrylate and preservative complex uniformly, treating at 50-60° C. for 30-75 min to prepare a hydrogel solution; S4. Using bacterial cellulose-chitosan solution as the outer layer spinning solution, hydrogel solution as the middle layer spinning solution, and chitin nanocrystal solution as the inner layer spinning solution, a high-efficiency composite fresh-keeping material was prepared by multi-fluid coaxial electrospinning technology.
2. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: In step S1, the concentration of the chitosan solution is 1.5-4.0 wt %, and the concentration of the bacterial cellulose solution is 0.5-3 wt %.
3. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: In the step S1, the ratio of the bacterial cellulose solution to the chitosan solution is 1:(4-8).
4. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: The amount of borate added in step S1 is 2-4 wt%.
5. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: In the step S3, the amount of xanthan gum added is 1-3 wt%, the amount of dialdehyde xylose added is 1.5-2.5 wt%, and the amount of acrylate added is 1-4 wt%.
6. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: The addition amount of the preservative complex in step S3 is 5-10%, and the composition of the preservative complex is tea polyphenols+thymol+licorice extract, wherein the ratio of tea polyphenols:thymol:licorice extract is (1-3):(0.5-2.5):(1-4).
7. The method for preparing a high-efficiency composite fresh-keeping material according to claim 1, characterized in that: The specific conditions of the multi-fluid coaxial electrospinning technology in step S4 are: the flow rate of the outer layer spinning solution is 1.0-5.0 mL / h, the flow rate of the middle layer spinning solution is 1.0-2.0 mL / h, and the flow rate of the inner layer spinning solution is 0.1-1.0 mL / h.
8. A high-efficiency composite fresh-keeping material obtained according to the preparation method according to any one of claims 1 to 7.
9. Use of the high-efficiency composite fresh-keeping material according to claim 8 in food preservation.
10. Use of the high-efficiency composite fresh-keeping material according to claim 8 in preserving peach fruits.
Citation Information
Patent Citations
Composite nano fiber fresh-keeping film preparation and application thereof
CN108049027A
Core-shell type composite nanofiber membrane and preparation method and application thereof
CN112301542A